Upper Blepharoplasty for Dermatochalasis With or Without Resection of the Orbicularis Oculi Muscle, Preaponeurotic and Nasal Fat Pads: A Comparative Study - Viscardi, Juan A.; Giordano, Salvatore (SPRINGER, 2025)
Objective
Upper blepharoplasty is the gold standard procedure for upper eyelid dermatochalasis. Upper blepharoplasties procedures include removing the skin, orbicularis oculi muscle, preaponeurotic, or nasal fat pad. The purpose of this study is to report surgical outcomes and compare them to the most common techniques.
Material and Methods
A retrospective review of 386 consecutive patients who underwent upper blepharoplasty at Turku University Hospital from January 1st, 2015 to June 30th, 2017 was conducted. Data collected include patient demographics, surgical details, and details regarding the type and frequency of complications.
Results
During the study period, 51 upper blepharoplasties with orbicularis oculi muscle excision, skin, preaponeurotic and nasal fat pads removal (study group) and 335 upper blepharoplasties with skin only removal (control group) were performed. Non-parametric tests showed that operative time (M=60.2min; SD=11.7min) and return to work (M=8.0days; SD=3.1days) were significantly shorter in the control group. No significant differences in the total amount of complications were detected (7.8% vs 2.4%, p=0.075). Subjective patients' satisfaction was significantly higher in the study group (from 0-10, mean 8.3 vs 7.0, p=0.034).
Conclusions
When compared to skin-only blepharoplasty, upper blepharoplasty with orbicularis oculi muscle excision, removal of skin, preaponeurotic and nasal fat pad appears to be a safe surgery with improved patient satisfaction and without carrying on additional complications.
Level of Evidence III
This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.